1997
DOI: 10.1042/bj3260579
|View full text |Cite
|
Sign up to set email alerts
|

A novel type of glutathione peroxidase: expression and regulation during wound repair

Abstract: We have previously identified and cloned a novel keratinocyte growth factor (KGF)-regulated gene in human keratinocytes that encodes the human homologue of a bovine non-selenium glutathione peroxidase (GPx). To gain insight into the regulation of this gene in vivo, we isolated the murine homologue from a mouse skin cDNA library. In vitro transcription/translation demonstrated that the cDNA encodes a 27 kDa protein. Furthermore, we amplified by PCR a partial cDNA that most likely corresponds to a related gene. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
83
0
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(89 citation statements)
references
References 31 publications
3
83
0
3
Order By: Relevance
“…This molecule is widely expressed, occurring in high levels in the liver, lung, eye lens, and keratinocytes (1,2,10,(12)(13)(14)(15)(16)(17)(18), whereas reduced expression of PRDX6 can lead to cell death and tissue degeneration (10, 11, 15, 19 -22). PRDX6 has been implicated in maintenance of blood vessel integrity in wounded skin (23,24) and in development and progression of several diseases, including oxidative-induced cataractogenesis (25), psoriasis (12,26) atherosclerosis (22), and Parkinsonian dementia (27). Accumulating evidence indicates that expression levels of PRDX6 contribute to pathophysiology of cells and tissues.…”
mentioning
confidence: 99%
“…This molecule is widely expressed, occurring in high levels in the liver, lung, eye lens, and keratinocytes (1,2,10,(12)(13)(14)(15)(16)(17)(18), whereas reduced expression of PRDX6 can lead to cell death and tissue degeneration (10, 11, 15, 19 -22). PRDX6 has been implicated in maintenance of blood vessel integrity in wounded skin (23,24) and in development and progression of several diseases, including oxidative-induced cataractogenesis (25), psoriasis (12,26) atherosclerosis (22), and Parkinsonian dementia (27). Accumulating evidence indicates that expression levels of PRDX6 contribute to pathophysiology of cells and tissues.…”
mentioning
confidence: 99%
“…This peroxiredoxin is expressed in all tissues but at particularly high levels in brain, eye, testes, and lung (2,7,8). Expression of 1-cysPrx protein or mRNA is decreased in a mouse that is susceptible to experimental atherosclerosis (9) and is elevated in brains of patients with Parkinsonian dementia (10), sporadic Creutzfeldt-Jacob disease (11), and Pick disease (12), in lungs from newborns (13), in malignant mesothelioma (14), in the healing edge of skin wounds (15), and in experimental cellular premature senescence (16). 1-cysPrx can reduce phospholipid and other hydroperoxides (6) and protects against cellular membrane damage (17,18).…”
mentioning
confidence: 99%
“…Previous studies from our laboratory revealed a strong induction of prdx6 expression in cultured keratinocytes on treatment with keratinocyte growth factor. 19 In vivo, prdx6 is overexpressed in the hyperproliferative epidermis of skin wounds 20 and of psoriatic patients. 19 To determine the consequences of enhanced expression of this enzyme in keratinocytes, we generated transgenic mice overexpressing Prdx6 in the epidermis.…”
mentioning
confidence: 99%